Geotecnologias aplicadas na evolução do uso da terra na microbacia do Córrego Capivari - Botucatu (SP) - Campos, Sérgio [UNESP]; Cavasini, Raquel [UNESP]; Pissarra, Terreza Cristina Tarlé [UNESP]; Piroli, Edson Luís [UNESP]; Silva, Erivaldo Antonio da [UNESP] (My University, 2012)
The analysis of the use and covering of the soil, through information obtained by the remote sensing it is of great usefulness in the planning and administration of the ordered occupation and rational of the physical middle, besides it makes possible to evaluate and to monitor areas of preservation of natural vegetation. The work sought to obtain the evolution of the soil use of Stream Capivari watershed - Botucatu (SP), in the period of 44 years, tends as cartographic base: the letter planialtimetric (IBGE, 1969) used in the georreferencing, the vertical aerial photographs of 1962 and the satellite image of 2006. The software CARTALINX was used for conversion of the analogical information for digital and determination of the areas. The soil use showed that the pastures occupied 2/3 of the area. The pastures and the brushwoods represented most of the area of the watershed (91,67%). The aerial pictures and the satellite image allowed the mapping of the soil use, as well as they will be for futures regional plannings. The area is being conserved environmentally, once he comes covered with approximately 31% of forests. The high index of occupation of the soil for pasture (67,88%), it is reflex of the predominance of the regional livestock

A análise do uso e cobertura do solo, através de informações obtidas pelo sensoriamento remoto, é de grande utilidade no planejamento e administração da ocupação ordenada e racional do meio físico, além disso possibilita avaliar e monitorar áreas de preservação de vegetação natural. O trabalho visou obter a evolução do uso da terra da microbacia do Córrego Capivari - Botucatu (SP), no período de 44 anos, tendo como base cartográfica: a carta planialtimétrica (IBGE, 1969) utilizada no georreferenciamento, as fotografias aéreas verticais de 1962 e a imagem de satélite de 2006. O software CARTALINX foi utilizado para conversão da informação analógica para digital e determinação das áreas. O uso da terra mostrou que as pastagens ocupavam 2/3 da área. As pastagens e as capoeiras representaram a maior parte da área da microbacia (91,67%). As fotografias aéreas e a imagem de satélite permitiram o mapeamento do uso da terra, bem como servirão para futuros planejamentos regionais. A área vem sendo ambientalmente conservada, uma vez que se apresenta coberta com aproximadamente 31% de matas. O alto índice de ocupação do solo por pastagem (67,88%), é reflexo da predominância da pecuária regional.
Geotechnologies applied in the evolution of the soil use of stream Capivari watershed – Botucatu (SP)
Keywords: Watershed; Remote sensing; Software CARTALINX; Microbacia; Sensoriamento remoto; Software CARTALINX